Pengaruh SPF terhadap Stabilitas dan Efektivitas Lip Balm Alami dari BEESWAX dan Minyak Kelapa - Naifah Nahda; Amraini Amelia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The lips are one of the most sensitive parts of the body and are highly vulnerable to damage from ultraviolet (UV) radiation from sunlight. Unlike other parts of the skin, the lips lack oil glands, making them more prone to dryness, chapping, and inflammation when not properly protected. One common method to maintain lip moisture and health is the use of lip balm. Natural lip balms made from ingredients such as beeswax and coconut oil are widely used due to their excellent emollient properties, which help moisturize and provide a protective layer on the surface of the lips. However, using natural lip balm alone may not be sufficient to offer complete protection, particularly against the harmful effects of UV rays. Therefore, innovation is needed by incorporating Sun Protection Factor (SPF) into natural lip balm formulations to enhance protection from sun exposure. This study aims to evaluate the effect of adding SPF to lip balm formulations based on beeswax and coconut oil, focusing on UV protection effectiveness, product stability, and moisturizing ability. The method involved formulating two types of lip balm—one with SPF and one without. UV protection effectiveness was tested using in vitro spectrophotometry, while moisturizing ability was assessed by measuring skin moisture content on the lips. In addition, physical characteristics such as texture, color, and stability under various storage conditions were analyzed. The results showed that the lip balm with added SPF provided significantly higher UV protection compared to the formulation without SPF. Furthermore, the addition of SPF did not reduce the moisturizing performance of beeswax and coconut oil and did not interfere with the overall product stability. In conclusion, integrating SPF into natural lip balm formulations is an effective innovation to enhance the protective function of lip care products without compromising their moisturizing benefits or user comfort. This combination provides a holistic solution for maintaining lip health while preventing UV-induced damage.